Research Progress of Metals and Alloys by Thermal Layering and Deposition - Srivastava, Ashish Kumar; Dixit, Amit Rai (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Today's world demands unique and specific materials for precise engineering applications. If there exist limitations in changing or altering materials, then the only option is to improve the existing ones. This Special Issue of Coatings, "Research Progress in Thermal Layering and Deposition", explores the various techniques related to surface coatings and similar surface modification techniques with a wealth of scientific and comparative results to better understand the current state of materials technology. The present volume also revels the opportunities and challenges associated with coatings techniques, and provides a futuristic approach to solutions.